Preconditioning Serum Levels of Endothelial Cell-Derived Molecules and the Risk of Posttransplant Complications in Patients Treated with Allogeneic Stem Cell Transplantation - Roald Lindås; Tor Henrik Andersson Tvedt; Kimberley Joanne Hatfield; Håkon Reikvam; Øystein Bruserud (Journal of Transplantation)
Endothelial cells are involved in the pathogenesis of acute graft-versus-host disease (GVHD) after allogeneic stem cell transplantation. These cells express several molecules that can be detected as biologically active soluble forms; serum levels of these molecules may thereby reflect the functional status of endothelial cells. Furthermore, acute GVHD is an inflammatory reaction and endothelial cells function as local regulators of inflammation. We therefore investigated whether differences in preconditioning/pretransplant serum levels of endothelium-expressed molecules (i.e., endocan, vascular cell adhesion molecule 1 (VCAM-1), and E-selectin) were associated with a risk of posttransplant GVHD. Our study should be regarded as a population-based study of consecutive and thereby unselected patients (n=56). Analysis of this pretreatment endothelium biomarker profile by unsupervised hierarchical clustering identified a subset of patients with increased early nonrelapse mortality. Furthermore, low endocan levels were significantly associated with acute GVHD in the liver and gastrointestinal tract, whereas high VCAM-1 levels were associated with acute GVHD in the skin only. Our study suggests that the preconditioning/pretransplant status of endothelial cells (possibly through altered trafficking of immunocompetent cells) is important for the risk and the organ involvement of later acute GVHD.